Algorithmic Authority and the Commodification of Religion: A Literature Review of the Shifting Islamic Broadcasting Ecosystem in the Artificial Intelligence (AI) Era - Suhaily Amri Hasibuan; Hasan Sazali; Muhammad Randicha Hamandia; Zhila Jannati (Indonesian Journal Publisher, 2026)
This study examines the transformation of Islamic Communication and Broadcasting in the era of Artificial Intelligence by focusing on algorithmic authority, religious commodification, and ethical crises in post-truth digital media. Using a qualitative library research design and critical discourse analysis, this article analyzes recent academic literature on AI-based da’wah, digital religion, platform capitalism, religious authority, and Islamic communication ethics. The findings show that AI and platform algorithms do not merely function as technical tools for producing and distributing religious content; they also act as curatorial powers that shape visibility, legitimacy, and public trust in Islamic messages. This transformation shifts religious authority from sanad-based scholarly transmission toward algorithmically amplified popularity, creating risks of misinformation, sensationalism, and weakened epistemic responsibility. The study also finds that Islamic broadcasting is increasingly absorbed into the logic of digital commodification, where religious symbols, sermon clips, and preacher branding are repackaged as attention-based commodities. In response, this article proposes a critical-paradigmatic reconstruction of Islamic Communication and Broadcasting through AI literacy, ethical platform governance, maqaṣid-oriented digital infrastructure, and social-impact-based evaluation. The success of digital da’wah should therefore be measured not only by virality and audience reach, but also by truthfulness, moderation, verification, social cohesion, and spiritual responsibility